Evaluation of Ethanol Extract Tapak Dara Leaf (Catharanthus roseus L. ) for Antibacterial Activity against Skin Pathogens - Alhijrah, Yayu; Naid, Tadjuddin; Nuryanti, Siska (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Tapak dara leaves (Catharanthus roseus L.) are known to be efficacious for relieving muscle pain, antidepressants, as well as medicine for various diseases such as relieving swelling from wasp stings, nosebleeds, and sore throats, antidotes, antibacterials, and lowering blood pressure in humans because they contain chemical compounds such as essential oils, phenolic acids, flavonoids, tannins, and alkaloids. This study aims to determine the antibacterial activity of the ethanol extract of tapak dara leaves against bacteria that cause skin infections. This type of research is done in an experimental laboratory using the agar diffusion method, which is based on inhibiting the growth of bacteria that cause skin infections. The stages of this research began with sample preparation, screening for antibacterial extract activity, and testing the antibacterial extract activity at several concentrations against the test bacteria that cause skin infections. This study obtained the results that the ethanol extract of tapak dara leaves tested positive for inhibition of the growth of Staphyloccus aureus, Staphylococcus epidermidis, Pseudomonas aeroginosa, and Propionibacterium acne based on the extract screening results. The results of this study also showed that the ethanol extract of tapak dara leaves at a concentration of 40% had the greatest inhibition using the agar diffusion method based on the diameter of the inhibition zone, with a value of 8.37 mm (Propionibacterium acne); 8.47 mm (Pseudomonas aeruginosa); 9.19 mm (Staphylococcus epidermidis); and 11.68 mm (Staphylococcus aureus)